New Media Literacy within the Context of Socio-Demographic Characteristics. (2016) - Arsenijević, Jasmina; Andevski, Milica
Abstract: The aim of research is to determine differences in media literacy competences in relation to socio-demographic characteristics of examinees from academic society in Serbia. This research was conducted in 2013 on 726 examinees. Hypotheses have been analysed by multivariate analysis of variant (MANOVA) and correlation analysis while testing differences in professions regarding incomes has been done by X 2 analysis. The results show that there are significant differences in media literacy competences among examinees regarding gender, age, area of education and income. The results do not differ from the results of other cultural, economic and social contexts.